Analysis of the Promotion Strategy of Captain Zack Tourist Attraction in Sumedang District - Royani, Solihin; Gunawan, Wawan; Apriliasari, Lusiana (SINTESA, 2024)
The focus of this research is the analysis of promotional strategies at Captain Zack tourist attraction. This research aims to determine the implementation of promotional strategy activities, obstacles, and solutions at Captain Zack tourist attraction. This research uses a descriptive qualitative method approach. The data collection process was obtained through passive participatory observation and structured interviews with companies and visitors, while supporting data was obtained through documentation. The data analysis technique uses the Miles and Huberman model with steps including data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that Captain Zack has carried out six elements of promotional strategies, namely advertising, face-to-face sales, sales promotion, publicity, direct marketing and word of mouth. There are several indicators in promotional strategy activities that have not been carried out optimally, especially in social media management. In current promotional activities, social media optimization must be done in order to reach a wider market.